Mating Behavior of Cyclocephala barrerai Martínez (Coleoptera: Melolonthidae) - Abraham Sanchez-Cruz; Patricia Villa-Ayala; Alfredo Jiménez-Pérez (Insects, 2025)
Our study aimed to characterize mating behavior in virgin and once-mated males and females of Cyclocephala barrerai. We reared the specimens under laboratory conditions and recorded the age at which the organisms began their reproductive activity and the time they remained active. We characterized behavioral acts during mating in two groups—virgin and once-mated organisms. Transitions between behaviors were analyzed using Markov chains and the generated ethograms. The duration of behaviors and the percentage of transitions were compared between the two groups. To characterize the mating behavior of C. barrerai, we adopted a framework commonly used in the literature, dividing mating behavior into three phases: premating, mating, and postmating. (A) Premating: Males search for females and mount and stimulate them, which the females resist through fighting behaviors. (B) Mating: The male mounts the female, which moves around and then stops; the male performs specific movements of the antennae and head and inserts his aedeagus into the female. (C) Postmating: Males exhibit guarding behavior over females. Although differences in pre- and postmating behaviors were observed between virgin and once-mated organisms, the duration of the acts did not show significant differences. These results provide key information on the reproductive behavior of C. barrerai, contributing to a better understanding of their biology and sexual interaction patterns.